Celebrating Masters & Johnson’s Human Sexual Response: A Washington University Legacy in Limbo - Susan Ekberg Stiritz; Susan Frelich Appleton (Washington University Journal of Law & Policy, 2017)
This Essay discusses how institutions devise traditions and celebrations within the context of protecting established hierarchies of power and privilege. Appleton and Stiritz bring to light the research of William Masters and Virginia Johnson and their publication of Human Sexual Response. The authors argue that Masters and Johnson’s work should be institutionally recognized and celebrated by Washington University. The Essay discusses how Washington University’s neglect has impacted Masters and Johnson’s narrative and reflects upon how their legacy was instead highlighted in the popular Showtime series Masters of Sex. Finally, the Essay reflects upon what might have been had the University celebrated their research through founding an institute in their honor.
Keywords: Washington University’s School of Medicine; research; William Masters; Virginia Johnson; Human Sexual Response; Washington University in St. Louis; Masters of Sex; Washington University